An investigation of behaviour during tacking‐up and mounting in ridden sports and leisure horses. (23rd January 2021) - Dyson, S.; Bondi, A.; Routh, J.; Pollard, D.; Preston, T.; McConnell, C.; Kydd, J. H.
Summary: Background: There has been no large‐scale, evidence‐based study on horses' behaviour while being tacked ‐up or mounted. Objectives: To describe equine behaviour during tacking‐up and mounting. Study design: Cross‐sectional, prospective observational study, using a convenience sample. Methods: A purpose‐designed protocol for documenting behaviour during tacking‐up and mounting was developed. Horses were recruited from 11 locations, from both amateur and professional riders. Horses (n = 193) were observed during acquisition of predefined information from the owners. Behaviour data were recorded during bridling, placement of the saddle, girthing and mounting. Results: The majority (67%) were bridled first. The median sum of abnormal behaviours during tacking‐up was 10/64 (interquartile range [IQR] 7.13; range 0.33). There was an equal frequency of abnormal behaviours during bridling and saddling in 52% of horses; 34% of horses showed more abnormal behaviours during saddling than bridling; 15% of horses showed more abnormal behaviours during bridling than saddling. The duration of abnormal behaviours related to total tacking‐up time was 25–75% in 51% of horses. There was a positive relationship between the sum of abnormal behaviours and the duration of abnormal behaviours (P = 0.0001). Repeatedly chomping on the bit occurred most frequently during bridling (67%). Ears back (57–65%) and an intense stare (54–62%) were similar in all phases. Fidgeting was more common during saddle placement (32%) and girthing (21%), than bridling (9%). Tail swishing was more frequent during saddle placement (20%) and girthing (34%), than bridling (10%). Turning the head to the girth was only seen during saddle placement and girthing (11 and 40%, respectively), in addition to attempting to bite (5 and 15%, respectively) and rubbing the nose (8 and 21%, respectively). The median sum of abnormal behaviours during mounting was 1/30 (IQR 1.3; range 0.12). Main limitations: Absence of many nonlame horses with correctly fitting tack. Conclusion: Abnormal behaviour during tacking‐up and mounting was common.